Engineering graphics for degree - John, K.C (PHI Learning Private Ltd., 2011)
The book is divided into seven modules. A topic is introduced in each chapter of a module with brief explanations and necessary pictorial views. Then it is discussed in detail through a number of worked-out examples, which are explained using step-by-step procedure and illustrating drawings. Module A covers the fundamentals of manual drafting, lettering, freehand sketching and dimensioning of views. Module B describes two-dimensional drawings like geometrical constructions, conies, miscellaneous curves and scales. Three-dimensional drawings, such as projections of points, lines, plane lamina, geometrical solids and sections of them are well explained in Module C. Module D deals with intersection of surfaces and their developments. Drawing of pictorial views is illustrated in Module E, which includes isometric projection, oblique projection and perspective projections. Module F covers the fundamentals of machine drawing. Finally, in Module G the book introduces computer-aided drafting (CAD) to make the readers familiar with the state-of-the-art techniques of drafting.